Modulating antigen processing through metal–organic frameworks to bias adaptive immunity - Ezra Cho; Meredith A. Davis; Julia A. Nowak; Mayayi Izzo; Anna Maria Ferrante; Fanrui Sha; Julian S. Magdalenski; Omar K. Farha; Michelle H. Teplensky (Proceedings of the National Academy of Sciences, 2025)
Vaccines induce specific immunity through antigen uptake and processing. However, while nanoparticle vaccines have elevated uptake, the impact of intracellular protein release and how this affects processing and downstream responses are not fully understood. Herein, we reveal how tuning unmodified antigen release rate, specifically through modulation of metal–organic framework (MOF) pore size, influences the type and extent of raised adaptive immunity. We use two MOFs in the NU-100x series with 1.4 nm difference in pore diameter, employ facile postsynthesis loading to achieve significant internalization of model protein antigen ovalbumin ( ca. 1.4 mg/mg), and observe distinct antigen release and intracellular processing profiles influenced by MOF pore size. We investigate how this difference in release biases downstream CD8 + , T H 1, and T H 2 T cell responses. Ovalbumin-loaded NU-1003 induced 1.8-fold higher CD8 + :CD4 + T cell proliferation ratio and displayed 2.2-fold greater ratio of CD4 + T H 1:T H 2 cytokines compared to ovalbumin-loaded NU-1000. Antigen released from NU-1000 in vivo exhibited stronger antigen-specific IgG responses, which is dependent on CD4 + T cells (up to ninefold stronger long-term antibody production and 5.9-fold higher IgG1:IgG2a ratio), compared to NU-1003. When translated to wild-type SARS-CoV-2 receptor-binding domain (RBD) protein, RBD-loaded NU-1000 induced 60.5-fold higher IgG1:IgG2a compared to NU-1003. Wild-type RBD-loaded NU-1000 immunization also induced a greater breadth of epitope recognition compared to NU-1003, as evidenced by increased binding antibodies to the Omicron RBD variant. Overall, this work highlights how antigen release significantly influences immunity induced by vaccines and offers a path to employ unmodified antigen release kinetics to drive personalized protective responses.